2012
DOI: 10.1159/000335730
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fine Needle Aspiration Specimen Adequacy for High-Risk HPV Detection and Genotyping in Oropharyngeal Squamous Cell Carcinoma

Abstract: Objective: The aim of this study was to determine the adequacy of archived and fresh fine needle aspiration (FNA) specimens from metastatic head and neck squamous cell carcinoma (SCC) for the molecular detection and genotyping of high-risk (HR) HPV. Study Design: Thirty-seven specimens from 26 patients diagnosed by FNA with metastatic SCC were included as retrospective specimens [19 slides stained with Papanicolaou (Pap) and 18 with Diff-Quik® (DQ)]. Twenty fresh FNA specimens from 18 patients were included as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 18 publications
3
30
1
1
Order By: Relevance
“…This method requires minimal specimen preparation, eliminates the need to process limited specimens as cell blocks and delivers a quantitative result based on a standard threshold that allows for unambiguous scoring of samples as positive or negative. A few feasibility studies have pointed to the effectiveness of these assays in cytological samples of HNSCCs [26,27,28]. …”
Section: Fine-needle Aspirationmentioning
confidence: 99%
“…This method requires minimal specimen preparation, eliminates the need to process limited specimens as cell blocks and delivers a quantitative result based on a standard threshold that allows for unambiguous scoring of samples as positive or negative. A few feasibility studies have pointed to the effectiveness of these assays in cytological samples of HNSCCs [26,27,28]. …”
Section: Fine-needle Aspirationmentioning
confidence: 99%
“…Recently, detection methods previously validated for HPV cervical Pap testing including proprietary commercial methods such as Hybrid Capture II [82] and Cervista [83] have successfully detected HPV DNA in HNSCC using archival air-dried, alcohol-fixed, and liquid-based preparations. The most rigorous testing to date has been a feasibility test using Hybrid Capture II on cytologic material obtained from surgically resected HPV-associated HNSCC [82].…”
Section: Cytologic Diagnosis Of Hpv-associated Hnsccmentioning
confidence: 99%
“…Performing an assay for the presence of β-actin cellular DNA and examining the Cervista controls for low genomic DNA or a recorded "invalid" result in the cobas HPV DNA test identified 6 FNA samples as inadequate (Table 4). Adequacy of archived and fresh FNA samples for molecular testing has ranged from 44-87% in previous studies using the internal control of the Cervista HPV DNA assay [19][20][21]. The presence of HR HPV mRNA and/ or DNA or sufficient β-actin DNA in fresh FNA samples in our study showed an adequacy rate of 92%.…”
Section: Cobas Pcr Dna Testingmentioning
confidence: 54%
“…Both LDT's and commercial assays for the detection of HR-HPV DNA have been used on FNA samples. An LDT PCR has used MY09/11 primers [16], whereas the commercial DNA assays used Hybrid Capture (HC2, Qiagen) [17,18]; Cervista (Hologic) [19][20][21]; cobas PCR (Roche) [22,23] and the PCR genotyping INNO-LIPA Extra System Kit (Innogenetics) [24]. Accuracy of HPV testing of FNA compared results to the presence of p16 and HR HPV or HPV16 DNA in tumors using ISH.…”
Section: Introductionmentioning
confidence: 99%